Sampling approaches based on spot aerosol generation, Catapulting and Trapping combined to LIBS - Vadillo-Pérez, José Miguel; Burgos Palop, Clara; Purohit, Pablo; Fortes-Román, Francisco Javier; Delgado-Pérez, Tomás (My University, 2026)
Different strategies to handle samples and perfom LIBS analysis are described. Three approaches will be detailed that result extremelly helpful when dealing with heterogeneous samples that are intended to be analyzed by laser-induced breakdown spectroscopy (LIBS). The first one involves the spot-aerosol generation (SAG), where an aerosol of nano/microparticles is created locally by a low-energy laser pulse. These particles can be directly analyzed in gas phase (straight LIBS) , being optically-trapped for single-particle LIBS (Optical-Trapping LIBS, OT-LIBS) , or analyzed once collected in the substrate by optical catapulting followed by LIBS (Optical Catapulting LIBS, OC-LIBS). Additionally, acoustic trapping is being explored as a useful way to handle liquids or samples with size and density not compatible with optical traping.
Keywords: Espectroscopía de plasma inducido por láser; LIBS; Sampling strategies; Optical trapping; Optical catapulting; Acoustic trapping; Aerosol generation